Analysis Forms of Argument in Open Grand Final National University Debate Championship (NUDC) 2020 and Open Grand Final World University Debate Championship (WUDC) 2021 - Sefri Tania Salsabilah (Universitas Veteran Bangun Nusantara, 2021)
This research aimed to find out and describe forms of arguments mostly used by debaters in open grand final both NUDC 2020 and WUDC 2021. This research used descriptive qualitative method. The subjects were 8 debaters selected by a purposive sampling. The instrument of this study was observation checklist adapted from Steven Johnson’s theory. It was supported by a video recording downloaded from YouTube and transcript making from the video has been downloaded. The researchers used descriptive method to analyze the data. The result of this study showed that there were eight models of argument forms from eight debaters in video open grand final NUDC 2021, namely one simple model argument, two chain model arguments, four cluster model arguments, and one complex model argument. Meanwhile, in video open grand final WUDC 2021, there were twelve arguments from eight debaters namely three simple model arguments, one chain model argument, six cluster model arguments, and two complex model arguments. Also, the cluster argument model was the dominant model used in open grand final both NUDC 2020 and WUDC 2021.